Gender differences in the associations between insomnia and glycemic control in patients with type 2 diabetes: a cross-sectional study. Issue 4 (4th February 2019) - Ding, Chenzhao; Zhang, Jihui; Lau, Eric Siu Him; Luk, Andrea On Yan; So, Wing Yee; Ma, Ronald Ching Wan; Choi, Kai Chow; Chan, Juliana Chung Ngor; Wing, Yun Kwok; Kong, Alice Pik Shan
Abstract: Study Objectives: Insomnia is associated with insulin resistance and type 2 diabetes (T2D) in the general population. However, the associations between insomnia and glycemic control in T2D population are not consistently reported. In this study, we aimed to examine the associations between insomnia and glycemic control, and gender differences in these associations among Hong Kong Chinese patients with T2D. Methods: This was a cross-sectional study involving T2D patients recruited from the Hong Kong Diabetes Registry between July 2010 and June 2015. Glycemic control was estimated by fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c ). Participants with the Insomnia Severity Index score > 14 were considered as having insomnia. Results: A total of 3753 patients were recruited. Compared with patients without insomnia, patients with insomnia had higher levels of FPG and HbA1c . After adjustment for potential confounding factors, insomnia was associated with higher FPG and HbA1c in the entire cohort. There were significant interactions between insomnia and gender for FPG ( p = 0.001) and HbA1c ( p = 0.025) in the full model. Subgroup analyses found that men with insomnia had higher FPG [8.23 (7.85–8.61) mmol/L versus 7.50 (7.39–7.61) mmol/L, p < 0.001] and HbA1c [7.79 (7.57–8.02)% versus 7.45 (7.39–7.52)%, p = 0.005] than men without insomnia after adjusted for confounding factors, whereas such difference was not observed in women. Conclusions: T2D patients with insomnia had worse glycemic control than the patients without insomnia. The associations were particularly pronounced in men.